Classification and Current Management of Inner Ear Malformations - Levent Sennaroğlu; Münir Demir Bajin (Balkan Medical Journal, 2017)
Morphologically congenital sensorineural hearing loss can be investigated under two categories. Majority of the congenital hearing loss (80%) are membranous malformations. Here the pathology involves inner ear hair cells. There is no gross bony abnormality and therefore, in these cases, high resolution computerized tomography and MRI of the temporal bone reveal normal findings. Remaining 20% have various malformations involving the bony labyrinth and therefore, can be radiologically demonstrated by CT and MRI. The latter group involves surgical challenges as well as problems in decision making. Some cases may be managed by hearing aid, some need cochlear implantation while some cases are candidates for an auditory brainstem implantation. During cochlear implantation, there may be facial nerve abnormalities, cerebrospinal fluid leakage, electrode misplacement or difficulty in finding the cochlea itself. During the surgery for inner ear malformations, surgeon must be ready to modify the surgical approach or choose special electrodes for surgery. In the present review article inner ear malformations are classified according to the differences observed in the cochlea. Hearing and language outcome after various implantation methods is closely related to the status of cochlear nerve and a practical classification of the cochlear nerve deficiency is also provided